A study on commercial solid waste composition and generation rate in Indera Mahkota 16, Kuantan - Nurul Hafifah , Arifin (2013)
The rapid population growth and broad urbanization and industrialization in Malaysia have resulted in the increasing of the solid waste generated from year to year. As people have been living in settled communities, the generation and dumping of solid waste, or garbage, has become a very noticeable issue. The objectives of this study are to determine the characteristics of commercial solid waste generations and generation rate in indera Mahkota 16, Kuantan. Other than that, this study also aims to study the factors affecting commercial solid waste generation in the studied area. This study was conducted at the commercial area of Indera Mahkota 16, Kuantan. The commercial premises at the area were divided into two categories; service and product with 15 premises for each category. During this study, two different sampling methods were conducted to collect the required data. To obtain data for the solid waste characteristics and generation rate, a waste collection method was conducted. This method included waste separation, weighing the waste collected and the data were recorded in the prepared form within the duration of 28 days. The second method used was questionnaire distribution. The data gained from the questionnaire were to determine the factors affecting commercial solid waste generation. Based on the data collection, solid waste generation was highly produced by service type premise with the total of 463.7 kg/month for the 15 premises compared to the product type premise with the amount of 251.8kg/month for the 15 premises. The generation rates of solid waste at this studied area were also in the suitable range for urban area which were 0.53 kg/premise.day for product type category meanwhile 0.82 kg/premise.day for service type category. The attitude of the residents and also seasonal variations such as festive season are the main contributor to the amount of solid waste produced at the area.